2013
DOI: 10.1371/journal.ppat.1003657
|View full text |Cite
|
Sign up to set email alerts
|

New World Bats Harbor Diverse Influenza A Viruses

Abstract: Aquatic birds harbor diverse influenza A viruses and are a major viral reservoir in nature. The recent discovery of influenza viruses of a new H17N10 subtype in Central American fruit bats suggests that other New World species may similarly carry divergent influenza viruses. Using consensus degenerate RT-PCR, we identified a novel influenza A virus, designated as H18N11, in a flat-faced fruit bat (Artibeus planirostris) from Peru. Serologic studies with the recombinant H18 protein indicated that several Peruvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
974
2
26

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,178 publications
(1,064 citation statements)
references
References 44 publications
6
974
2
26
Order By: Relevance
“…Previous research has demonstrated that the bat-derived neuraminidase-like N10/N11 and haemagglutinin H17/H18 have different functions compared to their homologues in other influenza viruses . N10 and N11 lack sialidase activity on tested sialic-acidcontaining oligosaccharides Tong et al, 2013;Zhu et al, 2012), and the H17 and H18 proteins did not bind to the canonical sialic acid receptors Tong et al, 2013;Zhu et al, 2013). These results suggest that H17N10 and H18N11 are influenza-like viruses that are related to categorized influenza A viruses but seem incompatible in function and reassortment capability.…”
Section: Introductionmentioning
confidence: 89%
“…Previous research has demonstrated that the bat-derived neuraminidase-like N10/N11 and haemagglutinin H17/H18 have different functions compared to their homologues in other influenza viruses . N10 and N11 lack sialidase activity on tested sialic-acidcontaining oligosaccharides Tong et al, 2013;Zhu et al, 2012), and the H17 and H18 proteins did not bind to the canonical sialic acid receptors Tong et al, 2013;Zhu et al, 2013). These results suggest that H17N10 and H18N11 are influenza-like viruses that are related to categorized influenza A viruses but seem incompatible in function and reassortment capability.…”
Section: Introductionmentioning
confidence: 89%
“…Influenza A viruses (IAVs) are classified into subtypes based on the antigenic differences of the surface glycoproteins haemagglutinin (HA) and neuraminidase (NA) into 18 HA and 11 NA subtypes, with aquatic birds considered the natural hosts of all subtypes of except H17N10 and H18N11 viruses (Fouchier et al, 2005;Gamblin & Skehel, 2010;Tong et al, 2012Tong et al, , 2013Webster et al, 1992). IAVs of the H9N2 subtype are low-pathogenic viruses, and two geographically distinct lineages have been described -the North American and Eurasian lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Wild waterfowl are considered the natural IAV reservoir (Taubenberger & Kash, 2010) and a genetically distinct lineage of viruses has also been identified in bats (Tong et al, 2013). A swine-origin H1N1 IAV was responsible for the first pandemic of the twenty-first century (Rambaut & Holmes, 2009) and was associated with w200 000 human deaths (Simonsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%